TEACHING PRONUNCIATION IN ENGLISH LANGUAGE EDUCATION: AN ACADEMIC PERSPECTIVE - Abdurahmonova Hayitgul; Egamberdiyeva Hadicha; Furqatova Bonu (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Pronunciation is a fundamental component of second language acquisition, particularly in English language teaching, where effective oral communication is a primary goal. Despite its significance, pronunciation has historically received less attention compared to grammar and vocabulary. However, contemporary research highlights that systematic pronunciation instruction can significantly improve learners’ intelligibility and communicative competence (Celce-Murcia et al., 2010). The primary objective of teaching pronunciation is not to eliminate a learner’s accent, but to ensure intelligibility. According to Derwing and Munro (2005), intelligibility, comprehensibility, and accentedness are separate constructs. Intelligibility refers to how much a listener understands, while comprehensibility concerns how easy the speech is to understand. Therefore, pronunciation instruction should prioritize features that most affect communication, such as stress, rhythm, and intonation, rather than aiming for native-like perfection. There are two widely recognized approaches to teaching pronunciation: the intuitive-imitative approach and the analytic-linguistic approach. The intuitive- imitative approach emphasizes listening and repetition, allowing learners to imitate native speaker models. This approach can be effective in immersive environments. In contrast, the analytic-linguistic approach involves explicit instruction in phonetic features, including the use of phonemic symbols and articulatory explanations (Kelly, 2000).